PENERAPAN DIGITALISASI SISTEM INFORMASI MANAJEMEN DAPODIK DI UPTD SPNF SKB KOTA SALATIGA - Wiwik Dwi Widyawati; Noor Miyono (STKIP Subang, 2024)
Industry 5.0 continues to develop rapidly along with technological developments around us. The role of information technology must be able to meet organizational needs or data and system requirements that support the organization's business strategy. Management Information System is a system that processes organizational data and However, in its implementation there are several problems and challenges faced by the world of education related to digitalization, namely the professionalism of educational staff which is not yet optimal, learning strategies which are still conventional while the development of digitalization of education continues to grow, the challenge of improving the system school management information that needs to be improved, digitalization developments that must continue to be developed, as well as the challenges of advances in science and technology. Information that is useful for carrying out tasks within the organization. UPTD SPNF SKB Salatiga City in its education process also uses the dapodik management information system. Basic Education Data, hereinafter abbreviated to Dapodik, is a data collection system managed by the Ministry of Education, Culture, Research and Technology which contains data on schools, students, educators and educational staff, and educational substance whose data is sourced from schools which are continuously updated (update ) online. Problem formulation, namely: 1) What is the description of the implementation of digitalization of the dapodik management information system at UPTD SPNF SKB Salatiga City?, 2) What are the obstacles that occur when implementing digitization of the dapodik management information system at UPTD SPNF SKB Salatiga City? This research is field research, namely the author goes directly to the field to collect data about the implementation of digitalization of the Dapodik management information system at UPTD SPNF SKB Salatiga City. The result of the research is the implementation of digitalization of the management information system at UPTD SPNF SKB Salatiga City. Several examples have provided knowledge that has been applied. data on schools, students, educators and education personnel, and educational substance whose data comes from schools which are continuously updated online. The obstacles that occur with the implementation of this operation are the inaccuracy of time in the data input process, the application changes very quickly, namely frequent updates, the Dapodik usage guide is not detailed enough, does not explain in detail the sub menus in Dapodik, the impracticality of the Dapodik web is still semi-online, that is, you can only use 1 PC, filling in student grades in the Merdeka Curriculum has not been updated and still refers to K13, and there are too many websites connected via Dapodik which often makes operators confused, such as verval, sp.datadik, etc.